Prevelance of Helicobacter pylori in patients with of without dyspepsia and comparsion of different methods in the diagnosis of helicobacter pylori - Mehmet CİNDORUK; Simten AKALIN; Ümit Bilge DOĞAN; Yasemin KOŞAR; Fatih YAKARYILMAZ; Mustafa ÇAĞATAY; İ. Safa YILDIRIM (Turkish Journal of Gastroenterology, 2019)
-